State Systems Change in Prevention Resource Management. (September 2014) - Diana, Augie; Landy, Ann L.; Flanagan, Sean
Federally funded initiatives have provided resources to develop comprehensive substance abuse prevention strategies. Historically, most awards were made directly to communities. Beginning in 1997, the Substance Abuse and Mental Health Services Administration (SAMHSA) Center for Substance Abuse Prevention (CSAP) signaled a new direction. The State Incentive Grant (SIG) program saw grants awarded to states and territories who then distributed money to communities to support prevention program implementation. A primary goal of the SIG program was statewide coordination of prevention service delivery and resource mobilization. Over seven years, 40 states and US territories received SIG awards. The SIG program was based on the assumption that systems change, in the form of improved state-level coordination and resource mobilization, would result in improved community-level prevention and, ultimately, in improved substance use outcomes. Coordination was defined as collaborative efforts of state-level agencies and individuals with control over prevention resources that resulted in a plan for addressing substance use problems and populations at risk. Resource mobilization was defined as the leveraging and/or redirection of resources to support implementation of effective prevention strategies. A cross-site evaluation of the systems changegoals included a content analysis of grantees' report documents and ratings of grantee accomplishments along a scale of milestones leading to institutionalization. A majority of grantees (68 percent) achieved at least the first milestone in coordination and resource mobilization categories and they achieved more coordination milestones than resource mobilization milestones. Results are discussed in relation to the role of prevention systems change in achieving desired substance use–related outcomes.